Cytoplasmic accumulation of ELAVL1 is an independent predictor of biochemical recurrence associated with genomic instability in prostate cancer. Issue 3 (2nd November 2015) - Melling, Nathaniel; Taskin, Berivan; Hube‐Magg, Claudia; Kluth, Martina; Minner, Sarah; Koop, Christina; Grob, Tobias; Graefen, Markus; Heinzer, Hans; Tsourlakis, Maria Christina; Izbicki, Jakob; Wittmer, Corinna; et al.
Abstract : Background: ELAVL1 is an RNA binding protein involved in translation control, which might have a regulatory role in prostate cancer progress. Methods: To evaluate its impact and relationship with key genomic alterations, ELAVL1 expression was analyzed by immunohistochemistry on a tissue microarray containing 12, 427 prostate cancers. Results: The analysis revealed a mild to moderate predominantly nuclear immunostaining in normal prostate epithelium and an often higher both cytoplasmic and nuclear expression in cancer cells. Weak, moderate, and strong cytoplasmic ELAVL1 staining was found in 43%, 18%, and 3% of 10, 478 interpretable tumors. Strong ELAVL1 staining was linked to high Gleason grade, advanced pathological tumor stage, positive nodal status, and PSA recurrence ( P  < 0.0001 each). A combined analysis of the effect of nuclear and cytoplasmic ELAVL1 expression on PSA recurrence revealed that the association with patient outcome was entirely driven by cytoplasmic staining. ELAVL1 positivity was more frequent in cancers harboring TMPRSS2:ERG fusions found by FISH (78%) or showing immunohistochemical ERG expression (74%) than in cancers without ERG rearrangement (63%) or ERG expression (58%, P  < 0.0001 each). Strong cytoplasmic ELAVL1 staining was further linked to presence of PTEN, 5q21, 6q15, and 3p13 deletions ( P  < 0.0001 each), an observation consistent with cytoplasmic ELAVL1 accumulation in case of genomic instability. The prognostic role of ELAVL1 expression was independent of Gleason grade, T stage, N stage, surgical margin status, and preoperative PSA, irrespective of whether preoperative or postoperative variables were used for modeling. Conclusion: Our study identifies cytoplasmic accumulation of ELAVL1 as a predictor of adverse clinical behavior of prostate cancer independent of established clinico‐pathological parameters. Prostate 76:259–272, 2016 . © 2015 Wiley Periodicals, Inc.